2001
DOI: 10.1016/s0029-7844(01)01600-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of persistent occiput posterior position on delivery outcome

Abstract: Persistent occiput posterior position contributed disproportionately to cesarean and instrumental delivery, with fewer than half of the occiput posterior labors ending in spontaneous delivery and the position accounting for 12% of all cesarean deliveries for dystocia. Persistent occiput posterior position leads to a sevenfold increase in the incidence of anal sphincter injury. Use of epidural analgesia was not related to the malposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
1
18

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 12 publications
8
84
1
18
Order By: Relevance
“…Certains facteurs sont cités comme responsables d'un taux plus élevé de variétés postérieures persistantes : une petite taille [22], un âge plus avancé [22,23], une cicatrice utérine [22], l'antécédent d'accouchement en OS [24,25], un terme plus avancé [26] et l'analgésie péridurale [26][27][28].…”
Section: Discussionunclassified
“…Certains facteurs sont cités comme responsables d'un taux plus élevé de variétés postérieures persistantes : une petite taille [22], un âge plus avancé [22,23], une cicatrice utérine [22], l'antécédent d'accouchement en OS [24,25], un terme plus avancé [26] et l'analgésie péridurale [26][27][28].…”
Section: Discussionunclassified
“…Earlier studies have shown that the occipitoposterior position is a risk factor for third-degree perineal tears. 10,28 Other risk factors that have been found earlier have been primiparous, vacuum or forceps delivery, episiotomy, fetal birth weight > 4,000 g, and long duration of the second stage of labor. 1,5,[13][14][15][16] Sultan et al 29 have shown promising results of primary sphincter repair by using the overlap technique instead of end-to-end repair.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of labour, an occiput posterior (OP) position occurs in approximately 25% of fetuses in the cephalic position 1, 2, 3, 4. Persistent OP at delivery occurs in approximately 10% of fetuses 5, 6.…”
Section: Introductionmentioning
confidence: 99%